The Standards Association: A Hybrid Governance Structure Between Market and Network - Rouquet, Aurélien (Management international / International Management / Gestiòn Internacional, 2021)
Since the beginning of the 20th century, many standards associations have emerged. The purpose of this theoretical article is to demonstrate that standards associations can be seen as a governance structure, and to position this structure in the transaction cost theory. A standards association is defined as any formal organization set up to develop common standards. The operating logic of the standards association is for associates to design common standards, and then to make the adoption of these standards a criterion for entering into a transaction. The article shows that it is a hybrid structure between market and network.